Model Pengembangan Desa Wisata Tamansari Banyuwangi sebagai Upaya Pemulihan Ekonomi Desa Pasca Pandemi COVID-19 - Betty Silfia Ayu Utami (OECONOMICUS Journal of Economics, 2022)
This study aims to analyze the strategy for developing the Tamansari tourism village in an effort to recover the economy during the COVID-19 pandemic. The data analysis technique is in the form of SWOT analysis using a quantitative approach to identify strengths, weaknesses, opportunities, and threats of the Tamansari tourism village which is then weighted andscored to produce analysis matrices, diagrams and strategy recommendations through SWOT. The results of the study put the Tamansari tourism village development strategy in an effort to recover the economy during the COVID-19 pandemic as an aggressive strategy (SO strategy). The aggressive strategy developed is to increase the implementation of cultural events through good cooperation with universities and local governments as well as maintaining the locality and cultural treasures and customs of Tamansari Village, improving the quality of processed products and maintaining innovation, opening space for village digitization, increasing variety tourism support products, improve the quality of service to tourists. research explains that Tamansari tourism village has greater strengths and opportunities than its weaknesses and threats, this makes Tamansari tourism village a village that has the potential to be developed and able to contribute to improving the economy of local communities in efforts to recover the economy during the COVID-19